ISLAMIC POLITICAL PARTIES IN INDONESIA AND GREEN POLITICS: A COMPARATIVE STUDY OF PARTY PLATFORMS - Suwarko, Andi; Andi Suwarko (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article examines the relationship between Islamic political parties in Indonesia and greenpolitics, focusing on a comparative analysis of party platforms. The study investigates how these parties incorporate environmental concerns into their agendas, drawing from both Islamic principles and modern ecological challenges. By reviewing the platforms of key Islamic parties such as the Prosperous Justice Party (PKS) and the United Development Party (PPP),the research assesses their commitment to environmental protection, sustainability, and climate change action. Using qualitative content analysis of official documents, speeches, and policy statements, the study identifies similarities and divergences in how these parties approach ecological issues. The findings show different levels of priority given to environmental matters, with some parties integrating green politics more prominently, while others maintain a focus on more traditional religious and social issues. This comparative analysis underscores the potential for Islamic political ideologies to engage more deeply with global environmental conversations. The paper concludes by offering recommendations on how Islamic political parties can strengthen their role in addressing environmental sustainability in Indonesia, contributing to broader global efforts.